Children at War. - Agnew, Kate (Children's book author and editor) (Contemporary Classics in Children's Literature., 2001)
This book provides a critical appraisal of the treatment of war in children's reading during the 20th century, covering World War I, World War II and subsequent wars, including Vietnam, the Gulf War and the war in the Balkans.